Bioinspired Nanoemulsions Stabilized by Phosphoethanolamine and Phosphoglycerol Lipids - Caianiello, Carlo (Nanomaterials (Basel), 2020)
Water-in-oil (W/O) nanoemulsions stabilized by phospholipids (PLs) are increasingly exploited in a wide spectrum of applications, from pharmaceuticals to food and cosmetic formulations. In this work, we report the design and optimization of an innovative emulsion based on a mixture of phosphoethanolamine (PE) and phosphoglycerol (PG) PLs, inspired by the composition of the inner leaflet of a bacterial outer membrane. Using the natural oil squalene as the continuous organic phase, no additional emulsion stabilizer is needed. On the other hand, a small amount of Span 80 is required when dodecane is used. The obtained nanoemulsions are stable for at least two hours, thus allowing the droplet size and distribution to be characterized by Dynamic Light Scattering (DLS) and the lipid layer structure and dynamics to be analyzed by Electron Paramagnetic Resonance (EPR) spectroscopy. The results indicate that squalene shallowly intercalates among the lipid tail termini, being unable to deeply penetrate the adsorbed lipid monolayer. The altered lipid dynamics are proposed to be the reason for the enhanced emulsion stability, this paving the way to future implementations and possible applications.